Angiotensin II-induced oxidative stress resets the Ca2+ dependence of Ca2+-calmodulin protein kinase II and promotes a death pathway conserved across different species - Palomeque, Julieta (2009)
Rationale: Angiotensin (Ang) II-induced apoptosis was reported to be mediated by different signaling molecules. Whether these molecules are either interconnected in a single pathway or constitute different and alternative cascades by which Ang II exerts its apoptotic action, is not known. Objective: To investigate in cultured myocytes from adult cat and rat, 2 species in which Ang II has opposite inotropic effects, the signaling cascade involved in Ang II-induced apoptosis. Methods and results: Ang II (1 μmol/L) reduced cat/rat myocytes viability by ≈40%, in part, because of apoptosis (TUNEL/caspase-3 activity). In both species, apoptosis was associated with reactive oxygen species (ROS) production, Ca2+/calmodulin-dependent protein kinase (CaMK)II, and p38 mitogen-activated protein kinase (p38MAPK) activation and was prevented by the ROS scavenger MPG (2-mercaptopropionylglycine) or the NADPH oxidase inhibitor DPI (diphenyleneiodonium) by CaMKII inhibitors (KN-93 and AIP [autocamtide 2-related inhibitory peptide]) or in transgenic mice expressing a CaMKII inhibitory peptide and by the p38MAPK inhibitor, SB202190. Furthermore, p38MAPK overexpression exacerbated Ang II-induced cell mortality. Moreover, although KN-93 did not affect Ang II-induced ROS production, it prevented p38MAPK activation. Results further show that CaMKII can be activated by Ang II or H2O2, even in the presence of the Ca 2+chelator BAPTA-AM, in myocytes and in EGTA-Ca2-free solutions in the presence of the calmodulin inhibitor W-7 in in vitro experiments. Conclusions: (1) The Ang II-induced apoptotic cascade converges in both species, in a common pathway mediated by ROS-dependent CaMKII activation which results in p38MAPK activation and apoptosis. (2) In the presence of Ang II or ROS, CaMKII may be activated at subdiastolic Ca2+concentrations, suggesting a new mechanism by which ROS reset the Ca2+dependence of CaMKII to extremely low Ca2+levels.